Latina Women in Academia: Challenges and Opportunities - Abraído-Lanza, Ana F.; Echeverria, Sandra E.; Flórez, Karen R.; Mendoza-Grey, Sonia (Frontiers in Public Health, 2022)
Latina women and other ethnic and racial groups continue to be underrepresented in science, technology, engineering, and mathematics (STEM) fields, including public health. This underrepresentation of people from diverse backgrounds and lived experiences in academic public health and other scientific disciplines is a form of epistemic oppression, exclusion that hinders contribution to knowledge production and advancement. Our analysis of 2021 data from the Association of Schools and Programs of Public Health indicates that Latinos/as represented only 9.5% of all instructional faculty and 13.7% of all tenured faculty at schools and programs of public health. We discuss the ways in which sociopolitical contexts, family-level dynamics and gendered norms, and institutional contexts hamper Latinas’ full participation in academia. We propose solutions such as redefining metrics for success, leadership accountability, equity analyses, cluster hiring initiatives, and instituting structured mentoring and leadership programs. Bold actions are needed if we are to advance the scientific enterprise and address the diversity and equity problem in public health.